Assessing fundamental motor skills in Belgian children aged 3–8 years highlights differences to US reference sample. (22nd March 2016) - Bardid, Farid; Huyben, Floris; Lenoir, Matthieu; Seghers, Jan; De Martelaer, Kristine; Goodway, Jacqueline D.; Deconinck, Frederik J. A.
Abstract: Aim: This study aimed to understand the fundamental motor skills (FMS) of Belgian children using the process‐oriented Test of Gross Motor Development, Second Edition (TGMD‐2) and to investigate the suitability of using the United States (USA) test norms in Belgium. Methods: FMS were assessed using the TGMD‐2. Gender, age and motor performance were examined in 1614 Belgian children aged 3–8 years (52.1% boys) and compared with the US reference sample. Results: More proficient FMS performance was found with increasing age, from 3 to 6 years for locomotor skills and 3 to 7 years for object control skills. Gender differences were observed in object control skills, with boys performing better than girls. In general, Belgian children had lower levels of motor competence than the US reference sample, specifically for object control skills. The score distribution of the Belgian sample was skewed, with 37.4% scoring below average and only 6.9% scoring above average. Conclusion: This study supported the usefulness of the TGMD‐2 as a process‐oriented instrument to measure gross motor development in early childhood in Belgium. However, it also demonstrated that caution is warranted when using the US reference norms.